2009
DOI: 10.1007/s10597-009-9260-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Barriers to the Implementation of Evidence-Based Practice in Psychiatry to Inform Health Policy: A Focus Group Based Study

Abstract: This study aims to explore the obstacles to Evidence-Based Practice (EBP) experienced by Belgian Dutch-speaking psychiatrists. We used an inductive, qualitative research strategy. Thirty-nine psychiatrists participated in five focus groups organised between September 2004 and September 2006. Data-analysis was guided by a 'grounded theory approach'. Three major themes emerged from the data: (1) Characteristics of evidence, including the lack of (use of) evidence and the applicability of evidence; (2) Characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…This means that we do not know if the patients in the IG actually received a different treatment than those in the CG. Many studies have shown challenges in implementing new procedures [66,67]. On the other hand, there was a significant improvement in motivation for treatment in the IG which indicates that there was a difference in the interventions given between groups.…”
Section: Discussionmentioning
confidence: 99%
“…This means that we do not know if the patients in the IG actually received a different treatment than those in the CG. Many studies have shown challenges in implementing new procedures [66,67]. On the other hand, there was a significant improvement in motivation for treatment in the IG which indicates that there was a difference in the interventions given between groups.…”
Section: Discussionmentioning
confidence: 99%
“…The Clearinghouse employs four approaches , gathered from research in prevention and implementation sciences (Chorpita & Starace, 2010 ;Domitrovich & Greenberg, 2000 ;Hannes, Pieters, Goedhuys, & Aertgeerts, 2010 ) to reduce barriers to the use of evidence-based and informed practice: (1) development of an evidence-based program information repository with a implementation-focused fact sheet (i.e., "consumer report") about each program; (2) provision of proactive, solution-focused technical assistance; (3) fl exible consideration of what constitutes reasonable evidence that programs work; and (4) respect for local decision-making in the selection and implementation of evidence-based practice approaches.…”
Section: Accessing Available Resources: Clearinghouse For Military Famentioning
confidence: 99%
“…Nevertheless, there is anecdotal evidence that evidence-based practice is seen as more relevant for 'biological' psychiatry than for the more subtle, greyer areas of clinical practice (Cooper 2003;Hannes 2010;Jainer 2011). These 'greyer' areas might include a myriad of factors relating to the holistic patient/service user experience and to questions of diagnosis, prognosis and aetiology: factors that do not so easily lend themselves to the collection of scientific (particularly randomised controlled trial, RCT) evidence in assessing the efficacy of treatments (particularly drug interventions) more commonly associated with evidence-based practice.…”
Section: Declaration Of Interestmentioning
confidence: 99%